A holistic view of Shisper Glacier surge and outburst floods: from physical processes to downstream impacts. Issue 1 (1st January 2021) - Muhammad, Sher; Li, Jia; Steiner, Jakob F.; Shrestha, Finu; Shah, Ghulam M.; Berthier, Etienne; Guo, Lei; Wu, Li-xin; Tian, Lide
Abstract: We observed the surge velocity, terminus advance, lake formation and outburst, as well as its downstream impacts at Shisper Glacier in the Karakoram, Pakistan and suggest potential nature-based risk-reduction solutions. A recent surge started in late 2017 with increased velocity since April 2018 and a resulting terminus advance from June 2018. Bi-modal peak velocity of 19.2 ± 0.16 m/day was observed in April-May 2018 and May-June 2019. Also, the terminus advance blocked the river from the adjacent Muchuhar Glacier repeatedly since November 2018. Lake outbursts were observed in June 2019 and April 2020. Relying on observations of the lake area and peak discharge of 142 m 3 s −1 in 2019 and 85 m 3 s −1 April 2020, outburst were simulated using the BASEMENT software. Simulations and field observations show that even at high discharge, damages were mainly observed along the main river channel, causing strong bank erosion rather than widespread inundation of land. The ice-dammed lake is potentially hazardous until the blocked stream completely disappears in future. Our results suggest that the biggest lake outburst hazard lies in its erosion potential with damages to infrastructure closest to the river and large sediments transport to the downstream Hunza River.